Bodies of knowledge: connecting the evidence bases on physical activity and health inequalities. Issue 4 (1st October 2016) - Kay, Tess
ABSTRACT: This paper addresses the absence of social science perspectives in physical activity policy guidance. Physical activity is a universal health focus, a priority for global, regional and national agencies acting on public health (e.g. the World Health Organisation; WHO Regional Office for Europe; Public Health England). Current UK guidance about being physically active was published in 2011, during a period of intense economic downturn and 'austerity' welfare. Physical activity is known to be lowest among sectors of the population at the lower end of the social gradient, making marginalised and disadvantaged groups priorities for initiatives to raise activity levels. Although much emphasis was given to the robust scientific underpinning of the 2011 guidance, it failed to engage with either the national or global debate around health inequalities, and gave no consideration to the social processes affecting health. This paper considers this omission. It first overviews patterns of health inequalities and explains the potential contribution of physical activity to addressing them. It then reviews the content of UK physical activity guidance, examines the role of health behaviour research in informing them, and suggests a number of ways in which social science knowledge could have enhanced its analysis. The paper then considers the process of knowledge production which informed the guidance, and considers the value of incorporating research into the social determinants of health (SDH) into the evidence base that informs physical activity guidance. It concludes with suggestions about how this might be done.